Penerapan Metode Kauny Quantum Memory dalam Meningkatkan Hafalan dan Pemahaman Siswa Pada Pembelajaran Tahfiz di MI Nurul Qomar Palembang - Dini Febriani Sidauruk (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2019)
The problems that occur in Tahfiz learning at MI Nurul Qomar are memorization and students' understanding in the memorization process is still low, so we need a method that allows students to memorize. The purpose of this study was to improve students' memorization and understanding of the Kauny Quantum Memory method in the process of learning to memorize students at MI Nurul Qomar Palembang. This type of research is field research using quantitative research approaches and the design used is quasi-experimental. Data collection is done by oral tests, interviews, observations, and documentation, data analysis using T tests. The findings in this study are that learning Tahfiz in MI Nurul Qomar Palembang by applying the Kauny Quantum Memory method has a significant effect. This is evidenced by the hypothesis test that uses the t test, the value of t_count is obtained = 4.112 while ttable = 2.09. Therefore it can be concluded that t_count> t_table or 4,112> 2.09. Because t_calculate = 4.112 is greater than the price of ttable = 2.09 at a significant level of 5% with degrees of freedom n-2 (22-2 = 20). So H_o which states there is no significant influence with the application of the Kauny Quantum Memory method in improving students 'memorization and understanding in Tahfiz learning at MI Nurul Qomar Palembang is rejected, while H_a which states there is a significant influence with the application of the Kauny Quantum Memory method in improving students' memorization and understanding in Tahfiz learning at MI Nurul Qomar Palembang is accepted. So, the Kauny Quantum Memory learning method can be said as one of the effective learning methods to improve memorization and understanding of the Koran of students at MI Nurul Qomar Palembang.